The Influence of Human Resource Development, Work Motivation, and Employee Engagement on the Performance of Employees of the Binamarga and Water Resources Office of Tangerang Regency - Hadiwijaya, Dudung; Muttaqijijn, Imam; Rachman, Adithyar (International Journal of Science and Society, 2024)
Employee performance is one of the important factors in the success of an organization. Good employee performance can improve productivity, efficiency, and quality of organizational services. The purpose of this study is to examine the influence of human resource development, work motivation, and work discipline on employee performance at the Tangerang Regency Bina Marga and Water Resources Agency. This study used a quantitative design with a survey approach. The research sample was 100 randomly selected employees of the Tangerang Regency Bina Marga and Water Resources Agency. Data were collected through questionnaires distributed to respondents. The data that had been collected was then analyzed using the help of the SPSS statistical program. The results showed that human resource development and work motivation have a positive and significant effect on the performance of employees of the Tangerang Regency Bina Marga and Water Resources Office. For the work discipline variable, there is no influence on the performance of employees of the Tangerang Regency Bina Marga and Water Resources Agency.